2005
DOI: 10.1186/1476-7961-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Insulin allergy and resistance successfully treated by desensitisation with Aspart insulin

Abstract: A 25-year-old, with type I Diabetes Mellitus with a previous diagnosis of Protamine Allergy but not to human Insulin, started to notice anaphylactic reactions inmmediatly after bolus with Insulin. Skin prick and intradermal test were positive to all insulins. Skin tests to other potential allergens resulted negative. Examination after bolus of Human Insulin revealed urticaria. Daily insulin requirement were around 2-2,4 U/Kg/day. Slow desensitisation with Aspart insulin, the insulin with lowest size of skin te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 24 publications
0
20
0
1
Order By: Relevance
“…Specific immunotherapy has been used successfully to treat insulin allergy [27][28][29]. It has been associated with a decrease in IgE antibodies titers, although the reduction in serum IgE levels does not always prevent from the development of allergic symptoms [17].…”
Section: Management Of Insulin Allergymentioning
confidence: 99%
“…Specific immunotherapy has been used successfully to treat insulin allergy [27][28][29]. It has been associated with a decrease in IgE antibodies titers, although the reduction in serum IgE levels does not always prevent from the development of allergic symptoms [17].…”
Section: Management Of Insulin Allergymentioning
confidence: 99%
“…In a 25-year-old type 1 diabetic patient, after an initial diagnosis of protamine allergy, an allergy for all kinds of insulin (human, short-and long-acting analogues) was confirmed. A treatment with CSII and insulin aspart associated with oral corticoid therapy was used with success as a desensitisation method [73]. In a 50-year-old type 2 diabetic patient, allergic reactions presented at the local injection site.…”
Section: Csii With Insulin Analogues and Insulin Allergymentioning
confidence: 99%
“…These allergens include insulin molecule or excipients such as preservatives (i.e., metacresol), retardants (i.e., protamine sulphate), stabilizers (i.e., zinc), acid and base buffers, and isotonic agents (i.e., glycerol). 1,2 The advent of analog insulin has reduced the incidence of insulin allergy. Allergenicity of insulin has been proposed by chemical changes in terminal B chains which have been modified in analog insulin.…”
Section: Discussionmentioning
confidence: 99%
“…Allergenicity of insulin has been proposed by chemical changes in terminal B chains which have been modified in analog insulin. 1 It has been reported that the ability of analog insulin to reduce immunogenicity is associated with its rapid absorption rather than changes in the immunogenic epitopes itself. 1 Treatment of insulin allergy includes antihistamine and use of alternative insulin preparation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation